9,19-Cyclolanost-24-en-3-one,21,23-epoxy-21,22-dihydroxy (21R, 22S, 23S) from the Leaves of Lansium domesticum Corr cv Kokossan - Mayanti, Tri; Sianturi, Julinton; Harneti, Desi; Darwati, Darwati; Supratman, Unang; Rosli, Mohamad Mustaqim; Hoong, Kun Fun (MDPI, 2015)
As a part of our studies on triterpenoids compounds from Indonesian Meliaceae plants, we isolated and described two tetranortriterpenoids, kokosanolide A and C and three onoceranoid-type triterpenoids including, kokosanolide B, 8,14-secogammacera-7,14-diene-3,21-dione and 8,14-secogammacera-7,14(27)-diene-3,21-dione from the seeds and the bark of the species kokossan [12]. In further screening for triterpenoid compounds, we found that the ethyl acetate extract from the leaves of L. domesticum cv kokossan exhibited the presence of triterpenoid compounds, based on a phytochemical test using the Liebermann-Burchard reagent. We report herein the isolation and structure elucidation of the new cycloartan-type triterpenoid, 9,19-cyclolanost-24-en-3-one,21,23-epoxy-21,22-dihydroxy (21R, 22S, 23S) (1) from the leaves of the L. domesticum cv kokossan. The chemical structure of compound 1 was established by NMR data and X-ray diffraction, as well as by comparison with those related compounds previously reported.